Moral Distress in the Pediatric Intensive Care Unit: An Italian Study - Sannino, Patrizio; Giannì, Maria Lorella; Carini, Micaela; Madeo, Mario; Lusignani, Maura; Bezze, Elena; Marchisio, Paola; Mosca, Fabio (Frontiers in Pediatrics, 2019)
Introduction: There is paucity of data within the Italian context regarding moral distress in intensive pediatric settings. The aim of the present study was to assess the frequency, intensity and level of moral distress experienced by nurses working in a sample of pediatric intensive care units. Materials and Methods: A cross-sectional questionnaire survey was conducted in eight pediatric intensive care units in a northern Italian region. Moral distress was evaluated using the modified Italian version of the Moral Distress Scale Neonatal–Pediatric Version in a convenience sample of 136 nurses. Results: Nurses working in pediatric intensive care exhibit low-moderate moral distress, with values ranging from 3.58 to 5.84. Nurses who intended to leave their work due to moral distress experienced a level of moral distress 18.28 points higher than that of nurses who did not intend to leave their work due to moral distress (72.08±43.9 vs 53.8 ±33.6, p=0.03). Among the socio-demographic characteristics investigated, only gender was associated with moral distress level. Specifically, females experienced a level of moral distress 14.4 points higher than that of males (61.16±36.6 vs 46.76±37.78, p=0.03, respectively). Conclusions: This study provides insights into the level of moral distress experienced in pediatric intensive care units in Northern Italy. Further large studies are required to confirm these results and identify strategies to reduce the burden of moral distress in acute pediatric care settings.